CHONDROMALACIA PATELLAE: ETIOLOGY, DIAGNOSIS, AND TREATMENT – A NARRATIVE REVIEW - Jan Romaniuk; Michał Romaniuk; Julia Groszewska; Daria Julia Woszczyk; Agata Rapior; Kinga Lubomska; Patrycja Jagura; Agata Mytych; Marta Dziedziak; Łukasz Nosek (International Journal of Innovative Technologies in Social Science, 2026)
Chondromalacia patellae (CMP) is a degenerative disorder of the hyaline cartilage of the patella, forming part of the patellofemoral joint. Due to its key role in joint biomechanics, CMP commonly manifests as anterior knee pain and functional limitation, which can significantly impair patients’ quality of life. Early and accurate diagnosis, along with appropriate treatment, is crucial due to the very limited regenerative capacity of articular cartilage. This narrative review analyses current evidence regarding the etiology, diagnostic approaches, and treatment options for CMP, including conservative management, regenerative therapies (autologous chondrocyte implantation and mesenchymal stem cell therapy), and surgical interventions. A comprehensive literature search of the PubMed database (2010–2025) was performed, prioritising meta-analyses, systematic reviews, and randomised controlled trials relevant to the topic. CMP represents a complex degenerative condition requiring an integrated clinical and imaging-based approach. Magnetic resonance imaging is highlighted as the primary non-invasive diagnostic modality, while evidence supporting regenerative therapies remains promising but limited. Early recognition and tailored management strategies are essential to prevent disease progression and improve long-term functional outcomes.